Laughing tomatoes and other spring poems = Jitomates risueños y otros poemas de primavera : poems - Alarcón, Francisco X., 1954-2016 (Children's Book Press, 1997)
A bilingual collection of humorous and serious poems about family, nature, and celebrations by a renowned Mexican American poet.